INHIBITION OF THREE NOVEL RADIX SCUTELLARIAE EXTRACTS ON IMMEDIATE HYPERSENSITIVITY - LI, Xiaorong; Wang, Jiangning; Shi, Haiyun; Gao, Lei; wang, xueyan (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Radix Scutellariae, a few papers reported its pharmacology activities including alleviate small intestines smooth muscles spasm, sedation, antihypertensive effect. However, the inhibition of its different organic extracts on immediate hypersensitivity has not bee researched.Materials and Methods: To investigate the anti-immediate hypersensitivity of three extracts including ethanol extracts, acetone extracts, ethyl acetate extracts from Radix Scutellariae, four pharmacological screening model were chose, such as 4-Aminopyridine induced pruritus model, histamine-induced mouse paw edema model, PCA(passive cutaneous anaphylaxis) in ear of mouse, activie cutaneous anaphylaxismouse (mouse ear edema test), furthermore, total IgE level in the sensitized mice serum was evaluated deeply. Results: Ethanol group at 1.42g/kg and 0.71g/kg could greatly decrease the licking number to 1.2 and 12.7 respectively; also keep mice paw swelling at 0.29ml and 0.51ml at 15 min after injection of histamine. Both ear passive cutaneous allergic reaction and active cutaneous anaphylaxis-ear swelling test demonstrated that ethanol group exhibit great inhibition on immediate hypersensitivity.Low IgE level was found in ethanol group, but high in other two groups.Conclusion: The ethanol extracts exhibits obvious strong inhibition, however, the acetone ones and ethyl acetate showed a little.